2006
DOI: 10.1017/s0004972700040429
|View full text |Cite
|
Sign up to set email alerts
|

On slant curves in Sasakian 3-manifolds

Abstract: A classical theorem by Lancret says that a curve in Euclidean 3-space is of constant slope if and only if its ratio of curvature and torsion is constant. In this paper we study Lancret type problems for curves in Sasakian 3-manifolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 10 publications
(19 reference statements)
1
60
0
Order By: Relevance
“…Some results already known from [8] and [12] are reobtained with particular choices of the parameters; but to the best of our knowledge, until now there have been no general expressions for Legendre curves in Nil 3 nor for their curvature and torsion in S 3 .…”
Section: Preliminariesmentioning
confidence: 94%
See 2 more Smart Citations
“…Some results already known from [8] and [12] are reobtained with particular choices of the parameters; but to the best of our knowledge, until now there have been no general expressions for Legendre curves in Nil 3 nor for their curvature and torsion in S 3 .…”
Section: Preliminariesmentioning
confidence: 94%
“…They form a two parameters family (with parameters denoted as l and m) containing, among others, some remarkable 3-manifolds: R 3 , S 3 , S 2 × R, H 2 × R and the 3-dimensional Heisenberg group Nil 3 . Recently, several studies have been devoted to special submanifolds in these spaces: parallel surfaces [2], biharmonic curves [6], [12] and [13], constant angle surfaces [15], graphs of constant mean curvature [19], biharmonic surfaces [21], higher order parallel and totally umbilical surfaces [23].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen studied surfaces in hyperbolic 3-space H 3 with proper mean curvature vector fields in [9]. On the other hand, as the generalization of Legendre curve, the notion of slant curves was introduced in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper [10], we studied slant curves in Sasakian 3-manifolds. In [11], we have shown that biharmonic curves in Sasakian space forms are slant.…”
Section: Introductionmentioning
confidence: 99%